Relasi Kuasa, Modal, dan Politik Lokal: Studi Kasus Masyarakat Nelayan di Desa Bababulo, Kabupaten Majene, Sulawesi Barat - Zahra Latifah; Gustiana A. Kambo (Universitas Muslim Maros, 2025)
The patron client bond between punggawa (boat owners) and sawi (crew members) in Bababulo’s coastal community, Majene Regency, demonstrates how contemporary electoral politics have reconfigured longstanding patterns of exchange and moral obligation. This research underscores a significant shift in the basis of punggawa power, which no longer depends solely on economic assets, but increasingly on the capacity to convert social and symbolic resources such as trust, indebtedness, prestige, and protective roles into political capital that can effectively mobilize votes. Employing a qualitative approach, data was collected through in-depth interviews and participant observation with eleven purposively selected participants, including punggawa, sawi, village authorities, and local political figures. Narrative analysis was applied to uncover processes of meaning-making, power negotiation, and mobilization embedded in everyday interactions. The findings show that the authority of a punggawa is continually reinforced through longstanding moral debts and social trust, which later become political commitments during election periods. Punggawa act as intermediaries who link the fishing community to broader political structures, while sawi are not completely passive; they take advantage of electoral moments to negotiate social and economic gains. The study concludes that traditional patronage persists, but in a transformed form becoming more calculated and transactional while still rooted in moral norms and mutual dependence that have adjusted to the dynamics of modern democratic practice.